2015
DOI: 10.3747/co.22.2880
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Panels Continue to Confuse the Facts and Inject Their Own Biases

Abstract: Additional confusion has been added to the “debate” about breast cancer. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Indeed, the Canadian National Breast Screening Study (cnbss) concluded that there was no difference in 13-and 25-year survival between women who underwent screening using mammography plus cbe compared with cbe alone [5][6][7] ; however, those conclusions should be considered in the light that a cbe was performed before randomization and that the cbe had to be normal 8 . Data derived from the Ontario screening program suggested that mammography and nurse-performed cbe result in a higher sensitivity than mammography alone, but with more false positives 9 ; however, those results have minimal carryover in real-world practice because the cbes in that study were performed by nurses who had received special training, a situation that would be clinically applicable only at the cost of great effort 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the Canadian National Breast Screening Study (cnbss) concluded that there was no difference in 13-and 25-year survival between women who underwent screening using mammography plus cbe compared with cbe alone [5][6][7] ; however, those conclusions should be considered in the light that a cbe was performed before randomization and that the cbe had to be normal 8 . Data derived from the Ontario screening program suggested that mammography and nurse-performed cbe result in a higher sensitivity than mammography alone, but with more false positives 9 ; however, those results have minimal carryover in real-world practice because the cbes in that study were performed by nurses who had received special training, a situation that would be clinically applicable only at the cost of great effort 10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the phenomenon of arriving at contrary results can be observed in the more serious areas where mistakes can potentially be lethal. Kopans (2015) recently described how several panels of specialists on breast cancer provided contradictory analyses. In the methodological , 'The unrealistic realist philosophy.…”
Section: Contrary Results Despite the Same Datamentioning
confidence: 99%
“…Unfortunately, “alternative facts” have been generated about breast cancer screening that go back decades. Confusion has resulted from the misinformation that has been published due to poor peer review in some of the most prestigious journals [ 1 , 2 , 3 , 4 ]. These erroneous analyses are then reported to the public by the media, which is unable to understand some of the complexities of the claims being made, resulting in confusing messages.…”
Section: Introductionmentioning
confidence: 99%